2021
DOI: 10.1007/s42978-020-00095-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two Isometric Strength Training Methods on Jump and Sprint Performances: A Randomized Controlled Trial

Abstract: Purpose Isometric strength training (IST) with rapid non-sustained contraction (RIST) is effective in improving the ability to generate force rapidly. However, the neuromuscular adaptation of IST with sustained contraction (SIST) and RIST is not known. Therefore, the aim of the study was to compare the neuromuscular adaptations of RIST with SIST. Methods Thirty-three national floorball players (23.9 ± 3.1 years old; 1.69 ± 0.08 m; 64.6 ± 11.1 kg) were recruited for this study. Pre-and post-test included counte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 33 publications
3
24
4
Order By: Relevance
“…In addition, ISO only improved jump height of a non-countermovement jump [ 19 , 20 ]. These findings are in contrast with findings of other studies whereby ISO was shown to improve countermovement jump (CMJ) height [ 5 , 7 , 8 ]. This may be attributable to the fact that the ISO exercises used by Kubo et al [ 20 ] was single joint exercise and executed at submaximal intensity while the exercises used by Bimson et al [ 5 ] was executed at multiple joint angles, and that used by Lum et al [ 7 ] and Lum and Joseph [ 8 ] were multi-joint exercise executed with maximal effort.…”
Section: Introductioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In addition, ISO only improved jump height of a non-countermovement jump [ 19 , 20 ]. These findings are in contrast with findings of other studies whereby ISO was shown to improve countermovement jump (CMJ) height [ 5 , 7 , 8 ]. This may be attributable to the fact that the ISO exercises used by Kubo et al [ 20 ] was single joint exercise and executed at submaximal intensity while the exercises used by Bimson et al [ 5 ] was executed at multiple joint angles, and that used by Lum et al [ 7 ] and Lum and Joseph [ 8 ] were multi-joint exercise executed with maximal effort.…”
Section: Introductioncontrasting
confidence: 99%
“…These findings are in contrast with findings of other studies whereby ISO was shown to improve countermovement jump (CMJ) height [ 5 , 7 , 8 ]. This may be attributable to the fact that the ISO exercises used by Kubo et al [ 20 ] was single joint exercise and executed at submaximal intensity while the exercises used by Bimson et al [ 5 ] was executed at multiple joint angles, and that used by Lum et al [ 7 ] and Lum and Joseph [ 8 ] were multi-joint exercise executed with maximal effort. In addition, despite showing the difference in the effects of PLYO and ISO on jump performances and morphological changes, Burgess et al [ 19 ] and Kubo et al [ 20 ] did not provide data on the changes in force-time characteristics which can provide practitioners with better understanding and comparison of the adaptations to the two modes of strength training.…”
Section: Introductioncontrasting
confidence: 99%
“…The IsoSqT, IsoPress and IsoPull involved participants exerting maximal force against a stationary bar as fast and as hard as they could. Each repetition was held for 3 s with 3 s rest in between repetitions [21]. Participants performed the IsoSqT at similar knee flexion angle (~100 • ), IsoPress (~90 • ) and IsoPull (~120 • ) at similar elbow flexion angles, as they adopted when they were initiating the pull phase during 200mTT.…”
Section: Training Programmentioning
confidence: 99%
“…Investigating the effect of isometric stresses on the effectiveness of the jump, scientists have proven the positive effect of isometric stresses on the explosive power values [12]. In their study specialists Lum, Barbosa, Joseph, Balasekaran also described the positive effect of isometric loads with the duration of 3 s (SIST) on explosive power values [13]. S. Jadhav noted an increase in jump height due to the use of isometric training [14].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the influence of different methods of isometric loading (with fast (1 s) and long (3 s) voltage) on the development of explosive power was studied by Lum, Barbosa, Joseph, Balasekaran [9]. The work proved the high efficiency of long-stress exercises for the explosive power development.…”
Section: Introductionmentioning
confidence: 99%